ANALISIS DAMPAK JANGKA PENDEK DAN PANJANG DARI INFLASI, SUKU BUNGA, DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Silfani, Dwi; Manihuruk, Frido Evindey; Sitohang, Gresia Septina; Oktania, Ainur; Sari, Arsiska; Nugrahadi, Eko Wahyu (Politeknik Bisnis Indonesia, 2024)
This research examines how inflation, interest rates, and government spending affect Indonesia's economic growth by utilizing the Error Correction Model (ECM) with time series data from 2000 to 2023. The processed data reveal that, in the short run, both inflation and interest rates negatively impact economic growth, showing coefficients of -0.009436 and -0.068359, respectively, though these effects are not significant in a statistical sense. In contrast, government expenditure has a notable positive effect, with a coefficient of 1.415698. Over the long term, managed inflation contributes a slight positive impact (0.015933), while interest rates persist in exerting a significant negative effect (-0.142703). Government expenditure maintains a robust positive effect, illustrated by a coefficient of 1.168041, highlighting the importance of effective budget management. This research offers empirical insights into the interactions of fiscal and monetary policies in fostering sustainable economic growth in Indonesia and provides actionable recommendations for policymakers to create effective strategies.